Cultural Symbolism in Regional Song Lyrics: Enhancing the Resilience of the Dayak Kanayatn Language - Ikhza Mahendra Putra; Hotma Simanjuntak (Universitas Islam Negeri Palopo, 2025)
The indigenous communities, including the Dayak Kanayatn, face significant challenges in preserving their language and culture amidst rapid modernization. The traditional Dayak Kanayatn songs are crucial in preserving their culture, as the lyrics contain valuable vocabulary, history, myths, and moral lessons. This study adopts a qualitative descriptive approach, utilizing Charles Sanders Peirce's cultural semiotics theory to analyze the signs, referents, and interpretants within the lyrics of nine Dayak Kanayatn songs to uncover their cultural values. The analytical methods employed include transcription of the lyrics, structural and semantic analysis of sentences, identification of cultural symbols, and evaluation of the objects referenced in the lyrics. The meanings derived from the analysis are examined to understand cultural and environmental resilience, and conclusions are drawn based on these findings. The traditional Dayak Kanayatn songs reflect cultural symbols that depict agrarian life, harmony with nature, skills, hard work, well-being, and gratitude. Additionally, these songs also reflect social solidarity, community identity, as well as the life cycle and belief in the universe.